(3MGTjI GdMafGhj Ydi TQM RcQjG GdCfUGQj Ydi GdNRQLjIs - (3jhSa Hf SGde Hf CMeO GdMafGhjs; (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdTGaYj , CHh jMji,J (B926 (3g` s
(3ChdgG (B:s
(3GeG HYO gPg MhGTj TQjaI hJYdjbGJ efjaI Ydi TQM GdNRQLjI aj Ydej GdYQhV hGdbhGaj s
(3BNQgG (B:s
(3hGfXQ Edi eGbjd hdG JfXQ Edi ef bGd hGdMeO ddg aj GdHOC hGdNJGe hGdUdGI hGdSdGe Ydi SjOfG eMeO hBdg hUMHg GdCYdGe s
(3GdfSNI HgG MhGTs
(3aJM QH GdHQjI dRcQjG GdCfUGQi hgh TQM ddQGeRIs
(3GfXQ cTa GdXfhf L (B2 (3U`(B1136 s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdYQhV hGdbhGais